Effect of micro- and nano-starch on the gel properties, microstructure and water mobility of myofibrillar protein from grass carp. (1st January 2022) - Li, Xuxu; Fan, Mingcong; Huang, Qilin; Zhao, Siming; Xiong, Shanbai; Yin, Tao; Zhang, Binjia
Graphical abstract: Highlights: NS and MS enhance MP gel properties, but with more significant effect from NS than MS. NS and MS different enhancement on MP gel is due to nano effect and microstructure. NS addition enhances the continuity of MP network, while MS was opposite. MS is embedded in MP with phase separation, while NS has good compatibility with MP. Decreased size of NS contributes more to MP gel performance than that of MS. Abstract: This work evaluated the effect of micro- and nano-starch (MS and NS) on the gel properties of fish myofibrillar protein (MP). Both MS and NS could enhance MP gel performance in terms of breaking force, elasticity and water holding capacity ( p < 0.05), with more significant effect from NS than MS. The difference between NS and MS in enhancement effect on MP gel is due to nano-size effect and different microstructures of MP/MS and MP/NS gels, with NS rather than MS contributing to the continuity of MP network. Synchrotron FTIR micro-spectroscopic images further verified that NS with large specific surface had good compatibility with MP, while MS was embedded in MP matrix with evident phase separation. Additionally, β-sheet still dominated the secondary structure of all gels, although adding both MS and NS could change molecular interactions, such as weakening ionic bonds and hydrogen bonds, and strengthening hydrophobic interactions.